Cultures of improvement in Scottish romanticism, 1707-1840
1 online resource (xiv, 247 pages)
Keywords: "The first applied research volume in Scottish Romanticism, this collection foregrounds the concept of progress as 'improvement' as a constitutive theme of Scottish writing during the long eighteenth century. It explores improvement as the animating principle behind Scotlands post-1707 project of modernization, a narrative both shaped and reflected in the literary sphere. It represents a vital moment in Romantic studies, as a 'four-nations' interrogation of the British context reaches maturity. Equally, the volume contributes to a central concern in the study of Scottish culture, amplifying a critical synthesis of Romanticism and Enlightenment. The conceptual motif of improvement allows an illumination of the boundaries (and beyond) of conventional notions of Romanticism, tracing its long, evolving imbrication with Enlightenment in Scotland. Exploring the holistic treatment of improvement in Scottish literature, chapter-studies include work on agricultural improvement and processes of commercialization, polite cultural renewal and the cotton trade, an expanding print culture and spirituality in death rituals. Taken as a whole, this amounts to an interdisciplinary re-consideration of the central role of improvement in Scottish cultural history of the long eighteenth century, of interest to a wide range of scholars, reflecting the vitality of the exchange between Enlightenment and Romanticism in Scotland."--Provided by publisher.